(untitled) (Journal of the College of Education for Women, 2019)
Abstract:If we neglect the value of historical fashions as a source of inspiration forcontemporary fashion designers we will neglect a treasure of original designs.In neglecting such a treasure how could we then know what is original. Todaythe most famous fashion designers are often inspired, in the outwardly fromand internal lines of their fashions, by fashion designed during the ages of thepast.Designers can find such fashions in books of history and museums. Butthe historical ages are not equal in the fertility of the originality and novelty oftheir fashions. Thus the contemporary designer may not find the old designsinspiring so he invents them.The researcher was keen in this paper to include all the basic concept ofthe art of patchwork 3? and she referred to the historical background of thisart as well as its common tools . She also referred to the art of embroideryand beadwork ... etc.To connect the pieces with this classy art (patchwork)/She discussed some modern producing techniques such as computer. (Thestudy ends with conclusion that suggests designs of the art of patchwork. thepaper included io suggested designs.)The study includes inventive ideas. In order words producing great varietyfrom one idea or design with great intellectual and expensive freedom andflexibility in prescribing the creative ideas that are original.The paper is of tow parts. First is the theoretical part which is chapter twoof the study that tackles the studies related to the subject mentioned above.The practical part includes a brief explanation of the steps of producing thedesigns and their supplements. This proves that the art of patchwork is abeautiful art, fit for artistic designs. Hence such designs are not less importantand beautiful than other designs that are not based on patchwork.The researcher likes to bring the old to the era of development andtechnology to make use of it and crystallize our artistic talents.Therefore the study aims to preserve the art of patchwork with the addition ofmodern and artistic touches with little cost as much as possible.